(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article provides information about the importance of motives in educational activities, classification of educational motives. Scientific theoretical concepts also have been cited in regard to the importance of educational motives in the academic activities of students В данной статье представлена информация о важности мотивов в учебной деятельности, классификация учебных мотивов. Также приводятся научные теоретические концепции, касающиеся важности учебных мотивов в учебной деятельности студентов